B Cells Are Required for Optimal CD4(+) and CD8(+) T Cell Tumor Immunity: Therapeutic B Cell Depletion Enhances B16 Melanoma Growth in Mice() - DiLillo, David J. (2010)
B lymphocytes can both positively and negatively regulate cellular immune responses. Previous studies have demonstrated augmented T cell-mediated tumor immunity in genetically B cell-deficient mice, suggesting that therapeutic B cell depletion would enhance tumor immunity. To test this hypothesis and quantify B cell contributions to T cell-mediated anti-tumor immune responses, mature B cells were depleted from wild type adult mice using CD20 mAb prior to syngeneic B16 melanoma tumor transfers. Remarkably, subcutaneous tumor volume and lung metastasis were increased two-fold in B cell-depleted mice. Effector-memory and IFNγ or TNFα-secreting CD4(+) and CD8(+) T cell induction was significantly impaired in B cell-depleted mice with tumors. Tumor Ag-specific CD8(+) T cell proliferation was also impaired in tumor-bearing mice that lacked B cells. Thus, B cells were required for optimal T cell activation and cellular immunity in this in vivo non-lymphoid tumor model. While B cells may not have direct effector roles in tumor immunity, impaired T cell activation and enhanced tumor growth in the absence of B cells argues against previous proposals to augment tumor immunity through B cell depletion. Rather, targeting tumor Ags to B cells in addition to dendritic cells is likely to optimize tumor-directed vaccines and immunotherapies.